Karakteristik Pemasaran Syariah Terhadap Kepuasan Nasabah Pada Bank Syariah Indonesia - Miranda, Julia; Fasa, Muhammad Iqbal (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2024)
This research aims to determine the characteristics of marketing on customer satisfactionat Indonesian sharia banks. The research approach that researchers use is a qualitativeapproach as a research procedure to obtain descriptive data. The data sources used are datathat can be obtained from in-depth interviews and searching for appropriate documents aswell as making observations, participants, data validity, then data analysis using datareduction, data presentation and concluding data. Based on the data analysis carried out,the research results show that the characteristics of sharia marketing on customersatisfaction are that the customers themselves feel satisfied with the products beingmarketed because the information provided by sharia bank marketing products is conveyedclearly and easily understood, there is no hidden information and the products are marketedopenly. directly by Bank Syariah Indonesia employees without subtracting or adding toinformation from the marketing product.